The Development of Learning Packages Using Metacognition Strategies to Enhance English Reading Comprehension for Sophomore English Student Teachers - Phoonsavat, Thanong Nong; Thipatdee, Goachagorn (Ubon Ratchathani Journal of Research and Evaluation, 2019)
The purposes of this research were to 1) develop the learning packages using metacognition strategies to enhance English reading comprehension for sophomore English student teachers based on the efficiency criteria of 80/80, 2) compare the students’ reading achievement before and after using the learning packages, 3) study the satisfaction of the students towards the learning packages. The sample, obtained through cluster sampling, consisted of 30 sophomore English student teachers in the first semester of academic year 2018 at Pakse Teacher Training College. The research instruments used in this study were 1) 6 learning packages, 2) 40 items of an achievement test with the difficulty indices between 0.27-0.68, the discrimination indices between 0.32-0.82, and the reliability value at 0.85, 3) 25 items of 5 Likert scales of the students’ satisfaction towards the packages. The statistics used for data analysis were mean, percentage, standard deviation, and t-test. The research findings were as follows: The efficiency of the developed learning packages was at 84.13/85.33. The students’ achievement after using the learning packages was significantly higher than that before using them at the .01 level. The students’ satisfaction towards the learning packages was at a higher level.